Jumlah Bakteri Asam Laktat Dalam Usus, Pertumbuhan dan Pemanfaatan Pakan Ikan Nila (Oreochromis niloticus) Dengan Penambahan Tepung Kulit Nanas (Ananas comosus) Dalam Pakan - Fitriani, Aulia; Sukarti, Komsanah; Agustina, Agustina (Jurnal Akuakultur Sungai dan Danau, 2024)
This study aims to analyze the effect of adding pineapple peel flour (Ananas comosus) at different doses on the number of lactic acid bacteria in the intestine, growth and utilization of tilapia (Oreochromis niloticus) fry feed. A Completely Randomized Design (CRD) consisting of four treatments with three replications was used in this research, namely the addition of pineapple peel flour at doses of 0%, 10%, 20% and 30% in the feed. Tilapia fish fry with an average weight of 8,27Â±0,36 g were reared in a 30 L aquarium with 13 fish each for 30 days, with feeding three times a day according to treatment. ad satiation. The results showed that the addition of pineapple peel flour at a dose of 10-30% increased the number of lactic acid bacteria in the intestines of tilapia fry, higher than at a dose of 0% (P<0.05), namely around 4.10-4.17 log CFU/ mL. A dose of 20% pineapple peel flour in the feed resulted in the highest weight growth, specific growth rate, feed efficiency level and protein efficiency ratio compared to other treatments (P<0.05), each at 14.56 g; 2.88 %/day; 77%; and 2.41%. This shows that pineapple peel flour has potential as a feed additive in tilapia cultivation.